Applications of smartphones and the mobile web in science and research - Torres-Salinas, Daniel (Anuario ThinkEPI, 2012)
One of the main internet trends is the increasing access to information through mobile devices, especially smartphones. The so-called mobile web is affecting all areas, including very versatile uses for scientific activity. The aim of this paper is to illustrate the use that the scientific community is making of the mobile web, firstly as an information and referral tool, with an analysis of leading mobile applications from publishers of scientific journals, databases and reference managers and secondly as a research tool and a data collection tool, among others.